Maternal Resilience: A Case Report of Cesarean Section One Week after Acute Myocardial Infarction - Firoozeh Madadi; Faranak Behnaz (Archives of Anesthesia and Critical Care)
Maternal morbidity and morbidity are among the most important concerns of the World Health Organization and every country’s healthcare system. Anesthetic management of parturients with a history of acute myocardial infarction (MI) presents unique challenges, particularly in the 3rd trimester when the pregnancy is approaching its end. Herein we will present anesthetic management of a parturient who underwent a cesarean section one week after acute myocardial infarction.